DAMPAK PSIKOLOGIS IBU SURI DALAM KONFLIK DRAMATISPADA NASKAH LAKON “ROH” KARYA WISRAN HADI - Puti Aryanti Soleha; Indrayuda (Universitas Negeri Padang, 2025)
This study examines the psychological impact of the character Mother Suri in the play ROH by Wisran Hadi through a psychoanalytic approach based on Sigmund Freud. The focus of the research is on the dramatic conflicts that affect the psychological condition of the main character. The method used is descriptive qualitative with content analysis techniques applied to the script text. The research results indicate six psychological impacts experienced by Mrs. Suri: (1) excessive anxiety about Suri's existence, (2) repression of past trauma, (3) projection of negative emotions onto others, (4) rationalisation of irrational actions, (5) sublimation of emotional energy through artistic expression, and (6) regression to childish behaviour. This emotional instability is triggered by the conflict between traditional beliefs and modern reality, as well as socio-cultural pressures. The findings reveal how internal conflicts (Id-Ego-Superego) shape the psychological dynamics of the character. This research contributes to the understanding of psychological characterisation in literature as well as the importance of mental health in society. The uniqueness of the research lies in the in-depth analysis of Mrs. Suri's character as a case study of individual inability to confront reality.